Renal involvement in canine leishmaniasis: a morphological and immunohistochemical study - Soares, M.J.V. [UNESP]; Moraes, J.R.E. [UNESP]; Moraes, Flávio Ruas de [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2009)
Caracterizou-se a deposição de IgG e IgM em rins de cães com leishmaniose visceral (LV) pelo uso da técnica imunoistoquímica. Foram estudados rins de 25 cães sintomáticos (caso) e de 15 cães assintomáticos (controle). Todos os animais foram positivos para leishmaniose pela reação em cadeia da polimerase, pelo ELISA e pela imunofluorescência indireta. Fragmentos renais foram submetidos à reação imunoistoquímica. Diversos padrões morfológicos de distribuição de grânulos subendoteliais de IgG e IgM foram identificados nos capilares glomerulares: global, segmentar, difuso ou focal. A intensidade da reação imunoistoquímica da IgG, medida pelo teste exato de Fisher não diferiu entre os grupos sintomáticos e assintomáticos e a intensidade de reação da IgM foi diferente entre os grupos (P<0,01). Depósitos de IgM nas células mesangiais e no infiltrado inflamatório raramente foram visualizados, no entanto as reações IgG foram freqüentemente visualizadas nesses locais. Concluiu-se que as reações de IgM foram mais intensas que as reações de IgG na LV canina e caracterizam-se pela distribuição de grânulos subendoteliais nos capilares glomerulares.

IgG and IgM deposits in kidneys of dogs with visceral leishmaniasis (VL) were studied in 25 symptomatic dogs (case) and 15 asymptomatic dogs (control) by an immunohistochemical method. All tested dogs were positive for VL by polymerase chain reaction, enzyme-linked immunosorbent assay, and indirect immunofluorescence test. Kidney fragments were submitted to immunohistochemical reaction. Many morphological patterns of distribution of subendothelial granules were identified for IgG and IgM in glomerular capillaries: global, segmental, diffuse, or focal. Intensity of immunohistochemical reaction to IgG was not significantly different when comparing the symptomatic and the asymptomatic animal groups by Fisher's exact test. IgM reactions were significantly different between groups (P<0.01). Deposits of IgM on mesangial cells and in inflammatory interstitial infiltrate were rarely seen, although IgG reactions were frequent at these sites. This study concluded that immunohistochemical reactions for IgM were more intense than those observed for IgG in canine VL, and these reactions were characterized by distribution of subendothelial granules in glomerular capillaries.
Envolvimento renal na leishmaniose canina: estudo morfológico e imunoistoquímico
Keywords: Dog; Leishmania; kidneys; Glomerulonephritis; Immunoglobulins; Cão; Leishmania; Rins; Glomerulonefrite; Imunoglobulinas